1971
DOI: 10.1021/bi00791a010
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of fructose 1,6-diphosphate, substrates, and monovalent cations with yeast pyruvate kinase monitored by changes in enzyme fluorescence

Abstract: SUELTERas attempting to distinguish between the substrate and coenzyme sites, and the essential and nonessential tyrosyl residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…In experiments where the effector concentrations were generally less than 1 mm, they showed that the dissociation constant of fructose bisphosphate was decreased 2.5-fold when 5 mM-ADP was added to solutions of the enzyme that contained 25 mM-Mg2+. Kuczenski & Suelter (1971a) regarded this result (which is in agreement with our findings) as surprising because of the observed insensitivity of ADP binding to an addition of 1 mM-fructose bisphosphate (Hunsley & Suelter 1969), which we referred to above when discussing Fit D1200. This is, therefore, an independent recognition of the possibility that the influence of fructose bisphosphate on yeast pyruvate kinase is fundamentally different at high and at low concentrations.…”
Section: Modelling the Datasupporting
confidence: 88%
See 2 more Smart Citations
“…In experiments where the effector concentrations were generally less than 1 mm, they showed that the dissociation constant of fructose bisphosphate was decreased 2.5-fold when 5 mM-ADP was added to solutions of the enzyme that contained 25 mM-Mg2+. Kuczenski & Suelter (1971a) regarded this result (which is in agreement with our findings) as surprising because of the observed insensitivity of ADP binding to an addition of 1 mM-fructose bisphosphate (Hunsley & Suelter 1969), which we referred to above when discussing Fit D1200. This is, therefore, an independent recognition of the possibility that the influence of fructose bisphosphate on yeast pyruvate kinase is fundamentally different at high and at low concentrations.…”
Section: Modelling the Datasupporting
confidence: 88%
“…The independence of the maximum velocity from the fructose bisphosphate concentration is already well-established for the yeast enzyme (Haeckel et al, 1968;Hunsley & Suelter, 1969;Johannes & Hess, 1973) and for the enzymes from rabbit muscle (Phillips & Ainsworth, 1977) and liver (Irving & Williams, 1973). The observation permits the conclusion that addition of effector does not decrease the molecular mass of the enzyme with its consequent inactivation (Kuczenski & Suelter, 1970, 1971a.…”
Section: Modelling the Datasupporting
confidence: 56%
See 1 more Smart Citation
“…The fluorescence of tryptophan residues within protein molecules is very sensitive to changes in environment and has been used to monitor subtle conformational changes within proteins (Waldeman et al, 1988). The tryptophanyl fluorescence quench exhibited by yeast pyruvate kinase on addition of Fru(1,6)P2 is profound and has been used successfully to monitor the binding of this allosteric effector to the enzyme (Kuczenski andSuelter, 1970, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…These included Na+, K+, Tris, and tetramethylammonium (TMA+). The latter two are generally nonfunctional in those enzyme systems that require K+ or Na+ for activity or conformational stability (Evans and Sorger, 1966; Kuczenski and Suelter, 1971), thus allowing for the maintenance of constant ionic strength without interfering with or mimicking specific K+ or Na+ effects.…”
mentioning
confidence: 99%